ANALISIS KELAYAKAN ELEVATOR STUDI KASUS HOTEL GRAND TJOKRO DAN MATARAM CITY YOGYAKARTA - Achmad Syaifudin, Sumardjito (Universitas Negeri Yogyakarta, 2014)
The purpose of the study ist o e x ami n e e l e v a t o r p a s s e n g g e r f o r Ho t e l GrandTjokro Yogyakarta (HGTY) building and Apartment and Hotel Mataram Yogyakarta rewards toelevator requirement as a condition of a residential building needs in terms of capacity, speedand amount. The approach of the study was case study. This study conducted by collectingbuilding data (builds drawing) and specifications of the building elevators. The Analysiselevators using 2 references plan, which are taken from the table chart of Benjamin Stein in thebook Mechanical And Electrical Equipment for Building (MEE) and the empirical way of HartonoPurbo (2007). Based on the analysis of table sandgraphsof MEE, the result of the study showedthat HGTY requires 2 lifts (1050 kg, 2 m/s), as well as to AHMCY needs 4 lifts (1000kg, 1.75m/s). While empirical manner indicates that HGTY need 3 lifts (1050kg, 0.63 m/s) and 2 lifts ifthe speed of 2m/s, as well as for AHMCY, elevators analysis is made of 1 zone system and 2zone system. The system needs to lift 1 zone as much as 2 pieces lifts for apartments and 3pieces lifts to the hotel, and for the 2 zone system each require 4 lifts (1000kg, 1.75 m/s). Basedon the MEE concluded that (1a) HGTY elevators, speed meets there quirements, but thenumbers cannot be analyzed, because speed does not fulfill the requirements for residentialbuildings. As for the (1b) AHMCY elevators, speed and capacity have fulfilled the requirements,but the number was not sufficient to fulfill there quirements. Based on empirical way concludedthat (2a) HGTY elevators have fulfilled there quirements interms of capacity and speed, but thenumber was not sufficient to fulfill the requirements, while for (2b) AHMCY elevators, speed,capacity and quantity to fulfill the requirement soft the system when made 1 zone, but thenumber was not sufficient to fulfill the requirements when made 2 zone system.Keywords: feasibility, multi-storey buildings, passenger elevators